Antioxidant activities of flavonoids isolated from the leaves of Tetracera indica Merr. - Sarian, Murni Nazira; Ahmed, Qamar Uddin; Murugesu, S.; Mat So'ad, Siti Zaiton (2016)
Different parts of Tetracera indica Merr. have been claimed by the folk medicine practitioners to have effectiveness in the treatment of diabetes mellitus and anti-inflammatory related diseases. In Malaysian traditional medicine system, the leaves are considered to lessen high blood pressure, diabetes and high fevers. Powdered leaves of T. indica were macerated with methanol for 72 h and then concentrated methanol extract was subjected to column chromatography (silica gel and sephadex LH 20) to afford three flavonoids (MN1, MN2, and MN5). MN 3 and MN4 were purchased for SAR study. Their structures were elucidated through the interpretation of spectroscopic data (NMR, IR, UV and MS). All compounds were further evaluated for antioxidant activities using rapid test by dot blot, DPPH and xanthine oxidase inhibitory assays. Compounds showed an antioxidant activity through dot blot, DPPH (1,1-diphenyl-2-picryl hydrazyl radical) and low inhibitory effect of xanthine oxidase. Among all five compounds, the MN5 showed the most potent SC50 (46.61) activity in rapid test by dot blot, DPPH, meanwhile MN1, MN4 and MN5 showed low inhibition of xanthine oxidase inhibitory assay. The results might be encouraging in future molecular studies, which could ultimately lead to better understanding the biological mechanism of action due to these compounds. Keywords: Tetracera indica Merr., phytoconstituents, antioxidant activities; DPPH, dot blot, xanthine oxidase inhibitory assay